A vanadium-titanium tailings-based clinker-free gelling material and preparation method thereof

Through the preparation of vanadium titanium tailings based clinker-free gelling materials, vanadium titanium tailings powder and titanium extraction slag are used to replace cement, the recycling problems of vanadium titanium tailings and titanium extraction slag is solved, and environmental pollution and engineering costs are reduced. The preparation of high-strength gelling mortar is achieved, which meets the compressive strength requirements of cement and reduces the cement usage and CO2 emissions.

CN118108431BActive Publication Date: 2025-01-14PANGANG GROUP MINING CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410251808.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-06
Publication Date
2025-01-14
Estimated Expiration
2044-03-06

AI Technical Summary

Technical Problem

In the prior art, vanadium titanium tailings and titanium extraction slag cannot be effectively recycled, resulting in problems of environmental pollution and high engineering costs, and the use of cement-based cementitious materials leads to increased CO2 emissions and costs.

Method used

Using vanadium titanium tailings based clinker-free gelling material and its preparation method, the gelling that meets the engineering needs is prepared by grinding vanadium titanium tailings powder and titanium extraction slag, and adding sulfur, calcium and silicon correction materials. Mortar completely replaces cement and reduces the amount of cement used.

Benefits of technology

The rational use of vanadium titanium tailings waste has been achieved, environmental pollution and engineering costs have been reduced, cement usage has been reduced, CO2 emissions have been reduced, the strength and stability of the cementitious material has been improved, and the compressive strength of 32.5 cement has been met. Require.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of tailings treatment, and in particular to a vanadium-titanium tailings-based clinker-free cementitious material and a preparation method thereof. A vanadium-titanium tailings-based clinker-free cementitious material comprises the following raw materials by weight: 200-250 parts of vanadium-titanium tailings powder, 120-160 parts of titanium slag, 30-60 parts of sulfur correction materials, 50-60 parts of calcium correction materials and 1-3 parts of silicon correction materials. The present invention uses the vanadium-titanium tailings powder produced by mining as a raw material, uses the titanium slag as a modifier and adds sulfur, calcium and silicon correction materials to make the cementitious system more stable and meet the strength requirements. The solid waste materials of the present invention, such as vanadium-titanium tailings powder, titanium slag, etc., meet the needs of the project and realize the reuse of solid waste materials. At the same time, the present invention uses vanadium-titanium tailings powder and titanium slag to completely replace cement, reduce the amount of cement used, reduce engineering costs, reduce carbon emissions, and achieve green environmental protection and resource recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tailings treatment, and in particular to a vanadium-titanium tailings-based clinker-free gelling material and a preparation method thereof. Background Art

[0002] Panzhihua is the main production area of ​​vanadium-titanium magnetite in my country, with rich mineral resources. The reserves of vanadium-titanium magnetite exceed 7 billion tons, and the reserves of titanium resources are 870 million tons, accounting for 90.5% of the country. A large amount of solid waste materials will be generated in the process of resource mining, and vanadium-titanium tailings are one of the important wastes. Titanium slag is an inorganic material with high titanium content and chlorine produced after high-temperature carbonization and low-temperature chlorination of titanium-containing blast furnace slag after mining. There are currently no economical and environmentally friendly measures to recycle this material. This results in the large-scale stacking and storage of vanadium-titanium tailings and titanium slag, but this storage method not only pollutes the environment, but also has the problem of large-scale land occupation and increased costs.

[0003] At present, the preparation of cementitious materials mainly relies on cement, and the large-scale use of cement will cause the following two obvious problems: (1) The production of cement inevitably generates CO 2 Emissions, my country's cement industry CO 2 The emissions of CO2 in 2022 will reach 1.379 billion tons, which is higher than that in 2020. 2 Therefore, under the guidance of national strategy, the use of cement should be gradually reduced, so as to achieve a decrease in cement production and thus reduce CO 2 (2) Cement production and use costs are high. The large-scale use of cement to prepare cementitious materials will increase project costs. For example, cement is used to prepare cementitious materials for filling mine voids, and the cost of cement accounts for 50% of the filling cost. Cement-based cementitious materials are one of the major problems currently faced. Therefore, the reuse of solid waste materials and the reduction of the use of cement-based cementitious materials have become issues that need to be urgently addressed today. Summary of the invention

[0004] In response to the above problems, the invention provides a vanadium-titanium tailings-based clinker-free cementitious material and a preparation method thereof, which solves the problem of large-scale use of cement. While not using or reducing the use of cement, the vanadium-titanium tailings and titanium slag produced by mining are reasonably utilized, reducing the damage to the environment caused by large-scale stacking of vanadium-titanium tailings waste, and the use of tailings waste also reduces engineering costs.

[0005] The present invention provides a vanadium-titanium tailings-based clinker-free cementitious material and a preparation method thereof, as well as a mortar prepared using the cementitious material and a preparation method thereof, which are achieved by the following schemes:

[0006] A vanadium-titanium tailings-based clinker-free gelling material comprises the following raw materials in weight fractions: 200-250 parts of vanadium-titanium tailings powder, 120-160 parts of titanium-extracting slag, 30-60 parts of sulfur correction materials, 50-60 parts of calcium correction materials and 1-3 parts of silicon correction materials.

[0007] Preferably, the main chemical components of the vanadium-titanium tailings powder are Fe 2 O 3 , CaO, SiO 2 、Al 2 O 3 、TiO 2 、V 2 O 5 and MgO, the specific surface area of ​​the vanadium-titanium tailings powder is 600-730m 2 / kg.

[0008] Preferably, the chemical composition of the titanium extraction slag is mainly CaO, SiO 2 、Al 2 O 3 、TiO 2 , MgO and MnO, the specific surface area of ​​the titanium slag is 600-650m 2 / kg.

[0009] Preferably, the sulfur correction material is gypsum, and the main chemical components of the sulfur correction material are CaO, SO 3 , Fe 2 O 3 、TiO 2 and SiO 2 .

[0010] Preferably, the main chemical components of the calcium correction material are CaO and MgO.

[0011] Preferably, the siliceous correction material is nano-silicon dioxide.

[0012] A method for preparing a vanadium-titanium tailings-based clinker-free gelling material comprises the following steps:

[0013] (1) Place the vanadium-titanium tailings powder in a grinding mill and grind for 2 to 12 minutes. The specific surface area of ​​the vanadium-titanium tailings powder is 600 to 730 m 2 / kg; the titanium slag is placed in a pulverizer and ground for 25 to 40 minutes. The specific surface area of ​​the titanium slag is 600 to 650 m 2 / kg;

[0014] (2) The ground vanadium-titanium tailings, titanium extraction slag, sulfur correction material, calcium correction material, and silicon correction material are mixed to prepare a vanadium-titanium tailings-based clinker-free cementitious material.

[0015] A mortar prepared using the above-mentioned cementitious material comprises the following steps:

[0016] (1) The above-mentioned cementitious material and machine-made sand are mixed evenly and poured into a mixer, and water is added and stirred to obtain mortar. The mass ratio of the cementitious material to the machine-made sand is 1:(3-4), and the weight proportion of the water is 200-230 parts.

[0017] (2) Fill the above mortar into the mold, demould after 48 hours, and cure under standard curing conditions

[0018] The vanadium-titanium tailings powder used in the present invention has a mineral phase analysis in which the main mineral components are kaolinite, feldspar, calcite, brookite and magnesite. It is found during grinding that when the specific surface area of ​​the tailings powder increases, the content of kaolinite and albite changes significantly, indicating that the mechanical activation has a significant effect on these two minerals, while the content of other components does not change significantly, which is an inert component in the tailings powder. In addition, the content of quartz in the tailings powder is small, so the SiO 2 It mainly exists in the form of feldspar and kaolinite minerals, which is also conducive to its activation by mechanical force.

[0019] During the grinding process, it was found that the specific surface area of ​​vanadium-titanium tailings powder had two peaks, namely 653.4m 2 / kg and 729m 2 / kg, and continued grinding has little effect on increasing the specific surface area of ​​the tailings powder. Therefore, the specific surface area of ​​the vanadium-titanium tailings powder used in the present invention is 600m 2 / kg and 730m 2 / kg, the 7d activity index of vanadium-titanium tailings powder under this specific surface area is 45.17% and 54.42% respectively.

[0020] Research on titanium slag shows that it contains a large amount of glass, so proper grinding can stimulate its activity. During the grinding process of titanium slag, it was found that the specific surface area of ​​titanium slag peaked at 635m 2 / kg. With the increase of grinding time, the specific surface area of ​​titanium slag decreases instead, and reverse crushing occurs, which means that the powder agglomerates and it is difficult to increase the specific surface area by further grinding. Therefore, the specific surface area of ​​titanium slag used in the present invention is 630m 2 / kg, the 7d activity index of titanium slag under this specific surface area is 121.5%.

[0021] Vanadium-titanium tailings are aluminum-rich materials with high early activity, which can ensure that the early strength of the prepared cementitious materials meets the requirements. However, due to the lack of silicon phase in the tailings powder, the hydrated calcium silicate gel material generated by the cementitious system is insufficient, which in turn leads to instability of the system. Therefore, a silicon correction material, nano-silicon dioxide, is added to supplement the missing silicon phase in the system, improve the crystal-gel ratio, and make the cementitious system more stable. Sulfur correction materials are added to supplement the missing sulfur phase in the system. Since the vanadium-titanium tailings themselves are aluminum-rich materials, after adding sulfur correction materials, the sulfur phase, aluminum phase, calcium phase, etc. in the liquid phase meet the conditions for the formation of calcium sulfonite, so that the cementitious system can generate calcium sulfonite in the early stage and provide early strength.

[0022] Although vanadium-titanium tailings can ensure early strength, the later strength is insufficient, so the present invention uses titanium-extracted slag to further modify the vanadium-titanium tailings-based cementitious material. Titanium-extracted slag can be activated in an alkaline environment, and as a late activator of the cementitious system, it supplements silicon and aluminum components in the late hydration stage to generate hydrated calcium silicate (aluminum) gel, fills the pores of the cementitious system, and reduces the porosity, thereby improving the late strength of the cementitious material.

[0023] Beneficial Effects

[0024] The present invention uses vanadium-titanium tailings powder produced by mining to prepare cementitious materials, uses titanium-extracting slag produced by mining as a modifier and adds sulfur, calcium, and silicon correction materials to make the cementitious system more stable and meet the strength requirements of 32.5 cement. The present invention uses solid waste materials such as vanadium-titanium tailings powder and titanium-extracting slag produced by mining to meet the needs of the project while realizing the recycling of solid waste materials, and reusing the waste to achieve the purpose of "turning waste into treasure". At the same time, the materials used in the present invention do not contain cement, and vanadium-titanium tailings powder and titanium-extracting slag are used to completely replace cement, reducing the amount of cement used, reducing project costs, and achieving green environmental protection and resource recycling. DETAILED DESCRIPTION

[0025] The following embodiments of the present invention are described in detail. The following embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0026] Example 1

[0027] A method for preparing mortar using vanadium-titanium tailings-based clinker-free cementitious material comprises the following steps:

[0028] (1) The vanadium-titanium tailings powder and titanium slag were ground for 2 min and 35 min respectively. The specific surface areas of the obtained vanadium-titanium tailings powder and titanium slag were 600 m 2 / kg and 630m 2 / kg.

[0029] (2) Weigh 200 parts of vanadium-titanium tailings powder, 160 parts of titanium slag, 35 parts of sulfur correction materials, 60 parts of calcium correction materials and 1 part of silicon correction materials respectively, mix the above materials, mix them evenly with machine-made sand in a mass ratio of 1:3-4, pour them into a mixer, and then add 220 parts of water and stir evenly to obtain mortar.

[0030] (3) The mortar prepared as above was filled into a mold, demolded after 48 hours, and cured under standard curing conditions (20±2°C, 95%±5% relative humidity) to obtain mortar T1 prepared using vanadium-titanium tailings-based clinker-free cementitious material.

[0031] Example 2

[0032] A method for preparing mortar using vanadium-titanium tailings-based clinker-free cementitious material comprises the following steps:

[0033] (1) The vanadium-titanium tailings powder and titanium slag were ground for 2 min and 35 min respectively. The specific surface areas of the obtained vanadium-titanium tailings powder and titanium slag were 600 m 2 / kg and 630m 2 / kg.

[0034] (2) Weigh 200 parts of vanadium-titanium tailings powder, 150 parts of titanium slag, 45 parts of sulfur correction material, 60 parts of calcium correction material and 2 parts of silicon correction material respectively, mix the above materials, mix them evenly with machine-made sand in a mass ratio of 1:3-4, pour them into a mixer, and then add 220 parts of water and stir evenly to obtain mortar.

[0035] (3) The mortar prepared as above was filled into a mold, demolded after 48 hours, and cured under standard curing conditions (20±2°C, 95%±5% relative humidity) to obtain mortar T2 prepared using vanadium-titanium tailings-based clinker-free cementitious material.

[0036] Example 3

[0037] A method for preparing mortar using vanadium-titanium tailings-based clinker-free cementitious material comprises the following steps:

[0038] (1) The vanadium-titanium tailings powder and titanium slag were ground for 2 min and 35 min respectively. The specific surface areas of the obtained vanadium-titanium tailings powder and titanium slag were 600 m 2 / kg and 630m 2 / kg.

[0039] (2) Weigh 200 parts of vanadium-titanium tailings powder, 140 parts of titanium slag, 55 parts of sulfur correction materials, 60 parts of calcium correction materials and 3 parts of silicon correction materials respectively, mix the above materials, mix them evenly with machine-made sand in a mass ratio of 1:3-4, pour them into a mixer, and then add 220 parts of water and stir evenly to obtain mortar.

[0040] (3) The mortar prepared as above was filled into a mold, demolded after 48 hours, and cured under standard curing conditions (20±2°C, 95%±5% relative humidity) to obtain mortar T3 prepared using vanadium-titanium tailings-based clinker-free cementitious material.

[0041] Example 4

[0042] A method for preparing mortar using vanadium-titanium tailings-based clinker-free cementitious material comprises the following steps:

[0043] (1) The vanadium-titanium tailings powder and titanium slag were ground for 12 min and 35 min respectively. The specific surface areas of the obtained vanadium-titanium tailings powder and titanium slag were 730 m 2 / kg and 630m 2 / kg.

[0044] (2) Weigh 200 parts of vanadium-titanium tailings powder, 160 parts of titanium slag, 35 parts of sulfur correction materials, 60 parts of calcium correction materials and 1 part of silicon correction materials respectively, mix the above materials, mix them evenly with machine-made sand at a mass ratio of 1:3-4, pour them into a mixer, and then add 220 parts of water and stir evenly to obtain mortar.

[0045] (3) The mortar prepared as above was filled into a mold, demolded after 48 hours, and cured under standard curing conditions (20±2°C, 95%±5% relative humidity) to obtain mortar T4 prepared using vanadium-titanium tailings-based clinker-free cementitious material.

[0046] Example 5

[0047] A method for preparing mortar using vanadium-titanium tailings-based clinker-free cementitious material comprises the following steps:

[0048] (1) The vanadium-titanium tailings powder and titanium slag were ground for 12 min and 35 min respectively. The specific surface areas of the obtained vanadium-titanium tailings powder and titanium slag were 730 m 2 / kg and 630m 2 / kg.

[0049] (2) Weigh 200 parts of vanadium-titanium tailings powder, 150 parts of titanium slag, 45 parts of sulfur correction materials, 60 parts of calcium correction materials and 2 parts of silicon correction materials respectively, mix the above materials, mix them evenly with machine-made sand in a mass ratio of 1:3-4, pour them into a mixer, and then add 220 parts of water and stir evenly to obtain mortar.

[0050] (3) The mortar prepared as above was filled into a mold, demolded after 48 hours, and cured under standard curing conditions (20±2°C, 95%±5% relative humidity) to obtain mortar T5 prepared using vanadium-titanium tailings-based clinker-free cementitious material.

[0051] Example 6

[0052] A method for preparing mortar using vanadium-titanium tailings-based clinker-free cementitious material comprises the following steps:

[0053] (1) The vanadium-titanium tailings powder and titanium slag were ground for 12 min and 35 min respectively. The specific surface areas of the obtained vanadium-titanium tailings powder and titanium slag were 730 m 2 / kg and 630m 2 / kg.

[0054] (2) Weigh 200 parts of vanadium-titanium tailings powder, 140 parts of titanium slag, 55 parts of sulfur correction materials, 60 parts of calcium correction materials and 3 parts of silicon correction materials respectively, mix the above materials, mix them evenly with machine-made sand in a mass ratio of 1:3-1:4, pour them into a mixer, and then add 220 parts of water and stir evenly to obtain mortar.

[0055] (3) The mortar prepared as above was filled into a mold, demolded after 48 hours, and cured under standard curing conditions (20±2°C, 95%±5% relative humidity) to obtain mortar T6 prepared using vanadium-titanium tailings-based clinker-free cementitious material.

[0056] The compressive strength of the mortars prepared in Examples 1-6 at 3d and 28d was tested according to the “Test Method for Strength of Cement Mortar (ISO Method)” (GB / T 17671-2020), and the test results are shown in Table 1.

[0057] Table 1 Compressive strength of mortar at 3d and 28d

[0058]

[0059] As shown in Table 1, in Examples 1-3 of the present invention, the specific surface areas of the vanadium-titanium tailings powder and the titanium-extracting slag are 600 m 2 / kg and 630m 2 / kg, the compressive strength of mortars T1, T2 and T3 prepared by using vanadium-titanium tailings-based clinker-free cementitious materials provided in Examples 1-3 can reach the strength requirement of 32.5 cement (in compliance with the "General Portland Cement" (GB175-2007)), and when the dosage of titanium-extracting slag tailings powder is gradually reduced and the dosage of sulfur correction material and silicon correction material is gradually increased, the compressive strength of mortar 28d prepared by using the above-mentioned cementitious materials gradually increases, among which the compressive strength of mortar T3 at 28d can reach 35.00MPa, which is 1.08 times higher than that of 32.5 cement.

[0060] In Examples 4-6, the specific surface areas of the vanadium-titanium tailings powder and the titanium slag are 730 m 2 / kg and 630m2 / kg, the compressive strength of the mortar is further enhanced, which proves that when the specific surface area of ​​vanadium-titanium tailings powder and titanium-extracting slag increases, the activity of both can be improved. The 28d compressive strength of mortar T6 can reach 36.07MPa, and the strength can reach the strength requirement of 32.5 cement.

[0061] The invention improves the mechanical properties of the overall cementitious material after the tailings powder is modified by titanium slag, sulfur correction material and calcium correction material. The maximum compressive strength can reach 36.07MPa at 28d, which is 1.11 times higher than that of 32.5 cement, and can meet engineering requirements.

[0062] In summary, the present invention uses a clinker-free cementitious material prepared based on vanadium-titanium tailings, and uses the cementitious material to prepare mortar, and its compressive strength can reach the requirements of 32.5 cement. It can replace 32.5 cement in certain fields, thereby reducing the amount of cement used and reducing carbon emissions. At the same time, it can also achieve the rational utilization of solid waste materials vanadium-titanium tailings, reduce the damage to the environment caused by large-scale stacking of vanadium-titanium tailings waste, save land resources, protect the environment, and reduce engineering costs and improve construction efficiency.

[0063] In the present invention, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0064] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A vanadium-titanium tailings-based clinker-free cementitious material, characterized in that: The invention comprises the following raw materials in weight fractions: 200-250 parts of vanadium-titanium tailing powder, 120-160 parts of titanium slag, 30-60 parts of sulfur correction material, 50-60 parts of calcium correction material and 1-3 parts of silicon correction material; the specific surface area of ​​the vanadium-titanium tailing powder is 600-730m 2 / kg; the specific surface area of ​​the titanium slag is 600-650m 2 / kg; The sulfur correction material is gypsum, and the main chemical components of the sulfur correction material are CaO, SO3, Fe2O3, TiO2 and SiO2; The main chemical components of the calcium correction material are CaO and MgO; The siliceous correction material is nano silicon dioxide.

2. The vanadium-titanium tailings-based clinker-free gelling material according to claim 1, characterized in that: The main chemical components of the vanadium-titanium tailings powder are Fe2O3, CaO, SiO2, Al2O3, TiO2, V2O5 and MgO.

3. The vanadium-titanium tailings-based clinker-free gelling material according to claim 1, characterized in that: The chemical components of the titanium-extracting slag are mainly CaO, SiO2, Al2O3, TiO2, MgO and MnO.

4. A method for preparing a vanadium-titanium tailings-based clinker-free gelling material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Place the vanadium-titanium tailings powder in a grinding mill and grind for 2 to 12 minutes. The specific surface area of ​​the vanadium-titanium tailings powder is 600 to 730 m 2 / kg; the titanium slag is placed in a pulverizer and ground for 25 to 40 minutes. The specific surface area of ​​the titanium slag is 600 to 650 m 2 / kg; (2) The ground vanadium-titanium tailings, titanium extraction slag, sulfur correction material, calcium correction material, and silicon correction material are mixed to prepare a vanadium-titanium tailings-based clinker-free cementitious material.

5. A mortar prepared using the cementitious material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) The cementitious material according to any one of claims 1 to 3 is mixed with machine-made sand and poured into a mixer, and water is added and stirred to obtain a mortar, wherein the mass ratio of the cementitious material to the machine-made sand is 1:(3-4), and the weight proportion of the water is 200-230 parts; (2) Fill the above mortar into the mold, demould it after 48 hours, and cure it under standard curing conditions.

Citation Information

Patent Citations

  • Mine underground filling mortar

    CN111196708A

  • Alkali-activated titanium slag extraction cement and preparation method thereof

    CN115180841A